Conjectures and refutations: Species diversity and phylogeny of Australoheros from coastal rivers of southern South America (Teleostei: Cichlidae) - Santos de Lucena, Carlos A.; Kullander, Sven; Norén, Michael; Calegari, Bárbara (PLOS ONE, 2022)
Morphological and genetic analyses of species of Australoheros focusing on those distributed in coastal rivers from the Rio de La Plata north to the Rio Buranhém, support recognition of 17 valid species in the genus. Eight species are represented in coastal rivers: A acaroides, A. facetus, A. ipatinguensis, A. oblongus, A. ribeirae, and A. sanguineus are validated from earlier descriptions. Australoheros mboapari is a new species from the Rio Taquari in the Rio Jacuí drainage. Australoheros ricani is a new species from the upper Rio Jacuí. Specimens from the Rio Yaguarón and Rio Tacuary, affluents of Laguna Merín, and tributaries of the Rio Negro, tributary of the Rio Uruguay are assigned to A. minuano pending critical data on specimens from the type locality of A. minuano. Australoheros taura is a junior synonym of A. acaroides. Australoheros autrani, A. saquarema, A. capixaba, A. macaensis, A. perdi, and A. muriae are junior synonyms of A. ipatinguensis. Heros autochthon, A. mattosi, A. macacuensis, A. montanus, A. tavaresi, A. paraibae, and A. barbosae, are junior synonyms of A. oblongus. Heros jenynsii is a junior synonym of A. facetus.